EPISTEMOLOGI MUHAMMAD SYAHRUR: PENAFSIRAN KONTEMPORER AL-QUR'AN - Hakim, Lukman (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2024)
Muhammad Syahrur, an Egyptian-Syrian scholar who offered various innovative and revolutionary theories in Islamic law and one of them was the Hudūd Theory (theory of legal boundaries) or Limit Theory. Syahrur is also one of the thinkers who took part in making takwil a method for understanding the Koran, especially for understanding the mutasyabihat verses. This research uses qualitative methods and is descriptive analysis, namely by examining the works of Muhammad Syarur. As a result of this research, there is one keyword that shows the epistemology adopted by Syahrur in his Islamic studies. The keyword is al-haqq (the right one). According to the shahrur, the Qur'an itself introduces the word al-Haqq and often contrasts it with al-Bathil (which is wrong). Syahrur is of the view that al-haqq and al-bathil are two contradictory things which are the basis for human knowledge. In constructing his methodology, Syahrur began his initial steps with a deaffiliation approach to the classical ulama's model of reading Al-Qur'anic texts.